Multiplet with components of different masses - Soroka, D.V.; Soroka, V.A. (Вопросы атомной науки и техники, 2007)
A principale possibility of the existence of a multiplet including the components with the different masses is indicated. This paper is dedicated to the memory of Anna Yakovlevna Gelyukh (Kalaida). Вказано на принципову можливість існування мультиплета, що містить компоненти з різними масами. Ця стаття присвячено пам’яті Ганни Яковлевни Гелюх (Калайда). Указана принципиальная возможность существования мультиплета, содержащего компоненты с различными массами. Эта статья посвящена памяти Анны Яковлевны Гелюх (Калайда).